2009
DOI: 10.1007/s00040-009-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Life expectancy and onset of foraging in the honeybee (Apis mellifera)

Abstract: Predictions that precocious foraging in honeybee workers is a result of shortening of their life expectancy were tested in both laboratory and field experiments. In the laboratory experiment, we assessed the impact of anaesthesia with CO 2 and infection with Nosema apis on the lifespan of workers. In the field experiment, the age at onset of foraging was observed in groups of workers with different expected lifespans. In both the experiments, workers originating from one queen inseminated with the semen of one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 77 publications
7
99
0
Order By: Relevance
“…Indeed, in the case of DWV, a direct influence on the behaviour of its host is not unlikely, given that DWV particles have previously been found in the mushroom bodies-a key higher brain centre of these insects [31] (but see [34] for a study where no behavioural effects were found). Irrespective of these possible adaptive causes, it is clear that precocious foraging would have a major effect on colony well-being, as premature foraging partially depletes the nurse bee population [63] and disrupts various activities inside the hive [64][65][66], and rapid behavioural maturation has been shown to strongly accelerate the failure of stressed honeybee colonies [63].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the case of DWV, a direct influence on the behaviour of its host is not unlikely, given that DWV particles have previously been found in the mushroom bodies-a key higher brain centre of these insects [31] (but see [34] for a study where no behavioural effects were found). Irrespective of these possible adaptive causes, it is clear that precocious foraging would have a major effect on colony well-being, as premature foraging partially depletes the nurse bee population [63] and disrupts various activities inside the hive [64][65][66], and rapid behavioural maturation has been shown to strongly accelerate the failure of stressed honeybee colonies [63].…”
Section: Discussionmentioning
confidence: 99%
“…However, the documented relation between behavior and life expectancy is correlative. Behavior may influence life expectancy (Rueppell et al 2007;Amdam et al 2009), but remaining life expectancy may also be a determinant of social behavior (Woyciechowski and Kozlowski 1998;Woyciechowski and Moron 2009;Kuszewska and Woyciechowski 2013). Regardless of causality, we also found evidence for an interaction between the social environment and the relation between social behavior and life expectancy.…”
Section: Discussionmentioning
confidence: 51%
“…The act of foraging is a perilous and metabolically challenging task that is typically carried out by worker bees in the later stages of life (Woyciechowski and Moroń, 2009). However, the timing of the role change from hive bee to forager can vary depending on the needs of the colony.…”
Section: Normal Biologymentioning
confidence: 99%
“…In addition, precocious foraging is correlated with shorter lifespans. Therefore, bees that forage earlier tend to do so at the expense of their longevity which could impact overall colony resource acquisition and productivity (Woyciechowski and Moroń, 2009). However, the relationship may be complex given that with seasonal variation, food availability, predation pressures, and adverse weather conditions that promote greater in-hive activity, older foragers can reverse their behavior, regenerate hypopharyngeal glands, and assume roles within the hive (Huang and Robinson, 1996).…”
Section: Normal Biologymentioning
confidence: 99%